Tutoring experiences of a high-risk newborn care simulation among nurse tutors and nursing student tutees in South Korea: a qualitative study - Hyun Young Koo; Bo Ryeong Lee; Hyeran An (Child Health Nursing Research)
Purpose This study aimed to explore tutoring experiences related to a high-risk newborn care simulation among nurses and nursing students to derive insights into developing effective neonatal nursing practice. Methods A qualitative content-analysis study was conducted in March 2023. Data were collected through narrative surveys and focus group interviews with four neonatal intensive care unit nurses and 12 senior nursing students participating in a 1-day high-risk newborn care simulation program. A content analysis was performed on the collected data. Results Three categories (“efforts to foster a sense of presence,” “efforts to promote positive awareness of the neonatal intensive care unit,” and “establishing one’s role as an educator”) and six subcategories were derived from the nurses’ responses. Three categories (“growth through a realistic virtual simulation,” “improved learning effects,” and “hope for continued development”) and six subcategories were derived from the nursing students’ responses. Conclusion The nursing students experienced realistic practice with their nurse tutors in the high-risk newborn care simulation, which helped them form their professional identity as future nurses. After tutoring, the nurses’ perceptions of nursing students changed positively, which affected their teaching methods.